Responsibilities of Pregnant Women for on Going Pregnancy - Medical Aspects - Matijević, Ratko; Erjavec, Katja (Medicine, Law & Society, 2016)
There are numerous factors known to affect the course of pregnancy and adversely impact perinatal mortality and morbidity. Some of them are avoidable and some are not. Avoidable factors can be either under responsibility of medical staff, health care systems and communities; or under responsibility of pregnant women. By modifying and changing their lifestyle, pregnant women can influence some avoidable factors and improve their pregnancy outcome. However, by ignoring them, they can cause potential damage to themselves and to their unborn child. There is no well defined responsibility for women concerning ways they influence their pregnancy outcome; they have a full right to make decisions about themselves and their unborn children, whether right or wrong. Good communication, education and understanding are essential when dealing with these issues.